Youth Employment: Does Life Begin at 16? - Michael, Robert T.; Tuma, Nancy Brandon (Journal of Labor Economics, 1984)
Theoretical economic models, official labor force statistics, and most empirical studies of young workers disregard employment experience of students under age 16. Evidence from several sources, however, suggests that students ages 14 and 15 acquire substantial employment experience. Moreover, that experience is vastly different for black and white youths. Several policy-related issues, including causes of black-white differences in adult earnings, may deserve to be interpreted differently in the light of differentials in early employment experience. This employment experience of 14- and 15-year-olds in general and its racial pattern in particular should not continue to be ignored.